Phase transition, microstructure and solidification of Ce–La–Fe and Ce–Nd–Fe alloys: Experimental investigation and thermodynamic calculation. (March 2023) - Su, D.; Yang, K.C.; Rong, M.H.; Liu, P.P.; Yao, Q.R.; Wang, J.; Chen, Q.; Rao, G.H.; Zhou, H.Y.
Abstract: In this work, phase transition temperatures of La–Fe and Ce–Fe alloys were determined using differential thermal analysis (DTA), while phase transition temperatures, microstructure, and phase compositions of La–Ce–Fe and Ce-Nd-Fe alloys were studied using DTA and scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS). Based on the available experimental data reported in the literature and the experimental results determined in this work, the La–Fe and Ce–Fe systems were re-assessed thermodynamically using the CALPHAD (CALcuation of PHAse Diagrams) method, and then the Ce–La–Fe and Ce-Nd-Fe systems were calculated by combining the re-assessed La–Fe and Ce–Fe systems with the previously assessed Nd–Fe, Ce–La, and Ce–Nd systems. The calculated phase diagrams and thermodynamic properties of the La–Fe and Ce–Fe systems are consistent with the experimental data. The calculated isothermal sections and vertical sections in the Ce–La–Fe and Ce-Nd-Fe systems are in good agreement with the experimental results. The solidification behaviors of Ce–La–Fe and Ce-Nd-Fe as-cast alloys were analyzed through the experimental examination and thermodynamic calculation with Scheil-Gulliver non-equilibrium model. The simulated results agree well with the experimental results. It indicates that the reasonable thermodynamic parameters of the Ce–La–Fe and Ce-Nd-Fe systems were obtained finally, which would be fundamental to developing a thermodynamic database of the multi-component Nd-RE-Fe-B alloy systems and then to designing novel Nd-Fe-B permanent magnets with light rare-earth metals La and Ce.